Modeling water resources management at the basin level: review and future directions - McKinney, D.C.; Xueliang Cai; Rosegrant, Mark W.; Ringler, Claudia; Scott, Christopher A. (International Water Management Institute, 1999)
The world is facing severe and growing challenges in maintaining water quality and meeting the rapidly growing demand for water resources. In addition, water used for irrigation, the largest use of water in most developing countries, will likely have to be diverted increasingly to meet the needs of urban areas and industry whilst remaining a prime engine of agricultural growth. Finally, environmental and other in-stream water demands become more important as economies develop. The river basin has been acknowledged to be the appropriate unit of analysis to address these challenges facing water resources management; and modeling at this scale can provide essential information for policy makers in their decisions on allocation of resources. This paper reviews the state of the art of modeling approaches to integrated water resources management at the river basin scale, with particular focus on the potential of coupled economic hydrologic models, and concludes with directions for future modeling exercises.